Presternal False Aneurysm Due to Osseous Arrosion of the Right Ventricle - Deschka, Heinz; Machner, Matthias; Wimmer-Greinecker, Gerhard (The Thoracic and Cardiovascular Surgeon, 2013)
Right ventricular rupture after open heart surgery is a rare but severe postoperative complication. In most cases, right ventricular bleeding is associated with mediastinitis and either directly caused by inflammatory processes or iatrogenically through penetration of dehiscent sternal edges or vacuum-assisted closure therapy. We describe a case of right ventricular rupture due to osseous arrosion in a closed chest in the absence of mediastinitis which led to the creation of a massive presternal false aneurysm.
Keywords: aneurysm; myocardial injury (includes blunt penetrating and iatrogenic); sternum; wound healing